Analisis Peningkatan Kapasitas Sumber Daya Manusia Melalui Program Pelatihan dan Pengembangan Berkelanjutan Pada Badan Kepegawaian dan Pengembangan Sumber Daya Manusia Kota Gunungsitoli - Serlin Yana Harefa; Palindungan Lahagu; Syah Abadi Mendrofa; Serniati Zebua (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to analyze the effectiveness of sustainable training and development programs in enhancing human resource capacity at the Badan Kepegawaian dan Pengembangan Sumber Daya Manusia (BKPSDM) Kota Gunungsitoli. The background of the study focuses on the need to improve the skills and competencies of regional government employees to achieve better performance and responsiveness to job demands. The research methodology employs a case study approach with data collection techniques including interviews, surveys, and document analysis. The results indicate that the training programs implemented at BKPSDM have had a positive impact on employee skills, work productivity, and job satisfaction. The findings also reveal several challenges in program implementation, such as resource constraints and resistance to change. This study contributes to the development of more effective and sustainable training strategies and offers recommendations for improving the implementation of training programs in government agencies. The main objectives of the training program are to enhance technical and professional competencies of employees, introduce new technologies, and build leadership capacity.